Decoloniality and indigenous tesstures - de Castro, Iara Quelho (2024)
The article deals with the politics articulation of the Terena, an indigenous ethnic group that lives in Mato Grosso do Sul. Through the analysis of documents that they formulate after each assembly, held annually since 2012, and from a decolonialist perspective, we seek to point out the ways of performance and positioning adopted in the face of the adversities they face. The analysis allows us to verify that the Terena weave their external political practices in different ways, highlighting their mastery of knowledge of the surrounding society.